A historical feeding ground for humpback whales in the eastern South Pacific revisited: the case of northern Patagonia, Chile. Issue 6 (15th March 2013) - Hucke‐Gaete, R.; Haro, D.; Torres‐Florez, J.P.; Montecinos, Y.; Viddi, F.; Bedriñana‐Romano, L.; Nery, M.F.; Ruiz, J.
ABSTRACT Since 2000, an increasing number of humpback whale sightings have been recorded in northern Chilean Patagonia (mostly between 41.5°S and 44°S) from dedicated aerial and marine surveys and also opportunistic and land‐based platforms during austral summer and autumn months. Based on local knowledge from the early years of coastal whaling suggesting the historic presence of humpback whales in the area, and more recent observations confirming feeding groups, mother–calf pairs, and philopatry, it is proposed that a proportion of the eastern South Pacific humpback whales consistently use the Chiloe‐Corcovado region to feed and nurse their young. This mid‐latitude area could be regarded as the northernmost feeding ground for humpback whales in South America, extending the previous known range some 1300 km north. These findings provide further evidence for alternative life‐strategies other than traditional migration and highlight the importance of northern Patagonian fjords to resolve questions that are central for large baleen whale conservation and management such as the extent and characteristics of spatio‐temporal habitat use and overlap with human activities. The need for future research on the migratory movements and population structure of this poorly understood population of humpback whales is emphasized, while an account is given of the threats they currently face. Copyright © 2013 John Wiley & Sons, Ltd.